2022
DOI: 10.3389/fchem.2022.956724
|View full text |Cite
|
Sign up to set email alerts
|

Comparison on Bioactivities and Characteristics of Polysaccharides From Four Varieties of Gastrodia elata Blume

Abstract: The composition, physicochemical properties, in vitro biological activity, and hypoglycemic activity exhibited by polysaccharides from four varieties of G. elata were investigated in this study; the four extracted GaE polysaccharides were termed as GaE-B (G. elata Bl. f. glauca S. chow polysaccharides), GaE-R (G. elata Bl. f. elata polysaccharides), GaE-Hyb (hybridization of G. elata Bl. f. glauca S. chow and G. elata Bl. f. elata polysaccharides), and GaE-G (G. elata Bl. f. viridis Makino polysaccharides). As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…G. elata Bl. f. elata polysaccharides possessed the highest hypoglycemic activity with the lowest glucose content and highest xylose content, which indicated that xylose was also an important kind of monosaccharide participating in the anti-diabetic process [ 191 ].…”
Section: Structure–activity Relationship Of the Anti-diabetic Effects...mentioning
confidence: 99%
“…G. elata Bl. f. elata polysaccharides possessed the highest hypoglycemic activity with the lowest glucose content and highest xylose content, which indicated that xylose was also an important kind of monosaccharide participating in the anti-diabetic process [ 191 ].…”
Section: Structure–activity Relationship Of the Anti-diabetic Effects...mentioning
confidence: 99%
“…For example, Pu’erh tea polysaccharides with the highest total phenol and protein content were reported to have the best antioxidation activity [ 26 ]. In another study on Gastrodia elata polysaccharides, it was shown that polysaccharides containing higher binding proteins and polyphenols (GaE-R) had higher antioxidant activity than polysaccharides containing higher total sugars (GaE-G) [ 27 ]. In addition to proteins and polyphenols, uronic acid in Litchi polysaccharides and Ampelopsis grossedentata polysaccharides have also been proven beneficial to antioxidant activity [ 28 , 29 ].…”
Section: Antioxidant Mechanism Of Natural Polysaccharides and Their D...mentioning
confidence: 99%
“…[32][33][34] Gastrodia elata polysaccharide (GEP) is the most abundant component in Gastrodia elata, which has the effects of anti-inflammation, anti-apoptosis, and enhancing immunity. [35][36][37] It was reported that GEP also regulated the composition of the gut microbiota. 36 However, whether GEP has the potential to play neuroprotective roles by affecting the gut microbiota and become a candidate to alleviate PD has not been reported.…”
Section: Introductionmentioning
confidence: 99%